Biallelic variant in cyclin B3 is associated with failure of maternal meiosis II and recurrent digynic triploidy. Issue 11 (16th September 2020) - Fatemi, Nayeralsadat; Salehi, Najmeh; Pignata, Laura; Palumbo, Pietro; Cubellis, Maria Vittoria; Ramazanali, Fariba; Ray, Pierre; Varkiani, Maryam; Reyhani-Sabet, Fakhreddin; Biglari, Alireza; Sparago, Angela; Acurzio, Basilia; et al.
Abstract : Background: Triploidy is one of the most common chromosome abnormalities affecting human gestation and accounts for an important fraction of first-trimester miscarriages. Triploidy has been demonstrated in a few cases of recurrent pregnancy loss (RPL) but its molecular mechanisms are unknown. This study aims to identify the genetic cause of RPL associated with fetus triploidy. Methods: We investigated genomic imprinting, genotyped sequence-tagged site (STS) markers and performed exome sequencing in a family including two sisters with RPL. Moreover, we evaluated oocyte maturation in vivo and in vitro and effect of the candidate protein variant in silico. Results: While features of hydatidiform mole were excluded, the presence of triploidy of maternal origin was demonstrated in the fetuses. Oocyte maturation was deficient and all the maternally inherited pericentromeric STS alleles were homozygous in the fetuses. A deleterious missense variant (p.V1251D) of the cyclin B3 gene ( CCNB3 ) affecting a residue conserved in placental mammals and located in a region that can interact with the cyclin-dependent kinase 1 or cyclin-dependent kinase 2 cosegregated in homozygosity with RPL. Conclusion: Here, we report a family in which a damaging variant in cyclin B3 is associated with the failure of oocyte meiosis II and recurrent fetus triploidy, implicating a rationale for CCNB3 testing in RPL.